CULTURE RESOPA TEMMANGINGNGI NAMALOMO NALETEI PAMMASE DEWATA IN AUDITORS PERFORMANCE IN MAKASSAR CITY - Misnawati Misnawati; Tenriwaru Tenriwaru; Amiruddin Amiruddin (Universitas Islam Balitar, 2017)
This study aims to determine the role of culture resopa temmangingngi namalomo naletei pammase dewata influential in the performance of auditors in the city of Makassar. This research is a research of data analysis of phenomenoligis paradigm, specializing in phenomenon and reality that seems to examine the explanation in it. In implementing a guideline in the profession to the stages of research that needs to be done, that is: Investigation, interviews, documentation, analysis, selection and from the first source or is valid. This study came to the conclusion of the analysis that the background of an auditor and the cultural values ​​ the of resopa temmangingngi namalomo naletei pammase dewata such as: Alempureng (honesty), Amaccang (intellectual), Asittinajang (propriety), Agettengeng (firmness), reso (effort), Siri ' (shame, self-esteem), Ada Tongeng (true speech), and Mappesona Ri Dewatae (resigned to the power of Allah SWT) give a strong influence in the performance of auditors.